Landscapes of Dionysos and Elysian Fields - Bonnechere, Pierre (Greek mysteries the Archaeology and Ritual of Ancient Greek Secret Cults, 2003)

Trophonius of Lebadea: mystery aspects of an oracular cult in Boeotia - Bonnechere, Pierre (Greek mysteries: the archaeology and ritual of ancient Greek secret cults, 2003)
The oracle of Trophonius at Lebadea is among the best documented ancient oracles, thanks to Pausanias. The Trophonion is not normally placed in relation to mystery cults, but several late sources say that mysteries were performed there. These texts do not represent a misunderstanding of a later period, nor a Hellenistic or Roman addition, but a legacy dating back at least to classical times. The sanctuary of Trophonius was conceived as an oracle like a mystery cult, both by its rites and by the nature of its revelation.